Preparing Global Trauma Nurses for Leadership Roles in Global Trauma Systems. Issue 5 (September 2017) - Muñiz, Sol Angelica; Lang, Richard W.; Falcon, Lisa; Garces-King, Jasmine; Willard, Suzanne; Peck, Gregory L.
Abstract : Trauma leads to 5.7 million annual deaths globally, accounting for 25%–33% of global unintentional deaths and 90% of the global trauma burden in low- and middle-income countries. The Lancet Commission on Global Surgery and the World Health Organization assert that emergent and essential surgical capacity building and trauma system improvement are essential to address the global burden of trauma. In response, the Rutgers Global Surgery program, the School of Nursing and Medicine, and the Robert Wood Johnson University Hospital faculty collaborated in the first Interprofessional Models in Global Injury Care and Education Symposium in June 2016. This 2-week symposium combined lectures, high-fidelity simulation, small group workshops, site visits to Level I trauma centers, and a 1-day training course from the Panamerican Trauma Society. The aim was to introduce global trauma nurses to trauma leadership and trauma system development. After completing the symposium, 10 nurses from China, Colombia, Kenya, Puerto Rico, and Uruguay were surveyed. Overall, 88.8% of participants reported high levels of satisfaction with the program and 100% stated being very satisfied with trauma lectures. Symposia, such as that developed and offered by Rutgers University, prepare nurses to address trauma within system-based care and facilitate trauma nursing leadership in their respective countries.